Investigating The Students’ Perception in Writing Class - Tenny Murtiningsih (UMBanjarmasin, 2022)
As one of the English skills, writing should be developed well in the teaching-learning process. Writing needs to give continuously to the students because developing writing skills needs a process. It needs time. Shortly, having good writing skills can’t be reached spontaneously. How to write the idea is still a problem for some students even to develop their idea in a paragraph or an essay in writing class. So in this research, the researcher wants to know the students’ perceptions in their writing class. The researcher invited 31 students for participants to answer the survey. There were 13 questions to answer in the questionnaire. The questionnaire was about their opinion in writing class, their motivation in writing class, teaching-learning process in writing class, writing media, and paragraph genre. Generally, the result of the survey shows that they love writing, still have a good motivation in writing class, and wants to develop their writing skill better